Development and Field Demonstration of a qPCR Panel for Heavy-Metal Detoxification Genes in Tomato from Irrigated Sites in Kano, Nigeria - Yusuf, Abubakar; Musa, Daniel D.; Kutawa, Abdullaziz B. (FUDMA Journal of Sciences, 2026)
Heavy-metal contamination of wastewater-irrigated farmland in the Kano River Basin notably lead, cadmium, chromium, nickel, copper and zinc has been characterised repeatedly at the soil and tissue level, but local molecular tools for monitoring how crops respond to it are lacking. This paper presents the development, validation and first field application of a multi-gene quantitative real-time PCR (qPCR) panel targeting phytochelatin synthase (PCS1) and glutathione reductase (GR-1) detoxification related genes with actin (ACT) as the reference gene in tomato (Solanum lycopersicum). Primer performance was established by serial dilution standard curves and melt-curve specificity analysis: ACT amplified with an efficiency of 90.6% (slope -3.57, R² = 0.998), PCS1 produced a single specific product (melt temperature 83.5 ± 0.0 °C; R² = 0.971), and GR-1 produced a single product at 81.1 ± 0.2 °C. Metallothionein-2 (MT-2) primers were excluded on specificity grounds. The validated panel was then applied to root and shoot tissue of field-grown tomato sampled in December 2025 from three contaminated sites along a rural-to-industrial gradient Challawa, Wudil and Dambatta and a control at Bayero University, Kano. Exposure was from natural field contamination rather than controlled dosing. GR-1 was preferentially expressed in roots and most strongly at the most contaminated site while PCS1 expression was more evident in shoot tissue patterns consistent with the metal partitioning documented in the same agroecosystem in earlier studies indicating that the panel returns biologically coherent signal. The panel provides a locally validated, low-cost tool for transcript-level monitoring of metal detoxification in field crops.